Restorative Justice Policy in Law Enforcement Against Perpetrators of Spreading Hoaxes Related to Elections on Social Media - Dian Rosita; Endang Setyowati; Suwandoko Suwandoko (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
General elections (elections) are a benchmark for the success of democracy for countries that adhere to democratic principles such as Indonesia. The large number of hoax issues surrounding the election that are spread via social media are often considered cybercrime or cybercrime. Meanwhile, criminal law is currently developing discussions about Restorative Justice, which offers forms of settlement with the aim of fulfilling the wishes of the parties with a win-win solution. The legal issue analyzed in this research is how restorative justice policies apply in enforcing the law against perpetrators of spreading fake news (hoaxes) related to elections on social media to see the possibility of using alternative dispute resolution for election violations, especially at the police level. The method used in this research is normative juridical, using literature study and a statutory and regulatory approach related to the legal issue being discussed. This research shows that the Restorative Justice Policy against perpetrators of spreading fake news (hoaxes) taken by the Police is carried out to create a clean, healthy and productive Indonesian digital space so as not to give rise to diversity in investigative administration and differences in interpretations of investigators and irregularities must be carried out in a persuasive, educational manner. so that there is no suspicion of criminalization in the criminal act of spreading fake news (hoax) against the perpetrator or in other words the person being reported.